Exposição ao risco cambial de empresas "Domésticas": evidências de Portugal e Alemanha - Ribeiro, Márcia Cristina Couto (2021)
Contrary to most studies on foreign exchange risk that so far have focused only on internationalized companies, this research work studies and analyzes the degree of foreign exchange exposure faced by "domestic" companies, and then, of companies whose amount of exports doesn´t exceed 5% of its total turnover each year. Concretely, examines the underlying determinants of exposure to foreign exchange risk obtained in the companies in the sample. It was considered, as a sample, Data from the Refinitiv Datastream databases of domestic companies in Portugal and Germany, and it should be noted that the companies that compose the sample, have a continuous operational history over the last 10 years, and are listed on the Portuguese (PSI Geral) and German (DAX) stock exchanges, respectively. In this way, the final sample consists of 1,368 German companies (151,716 company-month observations) and 70 Portuguese companies (9,371 company-month observations), over the time spectrum from January 2009 to December 2020. Expectedly, evidence shows that, in fact, German “domestic” companies and Portuguese “domestic” companies are, on average, exposed to EUR/USD exchange rate risk, being that, this degree of exposure is significantly and positively explained by Dimension. The sample for the German companies seems to suggest that larger companies are exposed to additional foreign exchange risk and that Gross Profit Margin, and Asset Turnover are negatively and significantly associated with exchange rate risk. On the other hand, it is the Portuguese companies with larger dimensions that are more exposed to exchange rate fluctuations.